STRATEGIES FOR INTERNAL QUALITY ASSURANCE IN SCHOOLS BY USING LEARNING ORGANIZATION CONCEPT UNDER PHRAPARIYATTIDHAMMA SCHOOLS GENERAL - Phatarayotphong, Nat; Roo-yuen yong, Wichian (Journal of Buddhist Anthropology, 2020)
The purposes of this research were: to create strategies of internal quality assurance in schools by using learning organization concept under Phrapariyattidhamma Schools, General Education, in the northeast region is mixed methods research. The sample group used in this research was Phrapariyatithamma Schools, General Education, in the Northeast region including 22 administrators and 332 teachers with the total number of 354 people. The sample size was determined by R.V. Krejcie & D.W. Morgan using stratified random sampling. The research instruments were a 5-level rating scale questionnaire with Index of Item–Objective Congruence (IOC) between 0.80-1.00 and reliability at 0.90. The statistics used for data analysis comprised percentage, mean, standard deviation and reliability. The research results were found that: Strategies for internal quality assurance of schools by using the concept of learning organization under Phrapariyattidhamma Schools, General Education, in the northeast region consisted of 7 strategies. Objective: Empower cooperation in the development of school standards to meet the educational standards set under the supervision and support of the agency .Strategy 1 Setting the education standard of the school Strategy 2 Planning of educational quality development according to quality standards Strategy 3: Implementation of the plan to the eye quality work, educational standards Strategy 4 Raising the assessment Results and monitoring of educational management Strategy 5 Monitoring the quality according to educational standards Strategy 6 Creating a self-evaluation report (SAR) Strategy 7 Enhancing capacity, driving power, continuous improvement of educational quality.